Associations between self‐reported sleep duration and sleeping disorder with concentrations of fasting and 2‐h glucose, insulin, and glycosylated hemoglobin among adults without diagnosed diabetes1 (在未诊断糖尿病的成年人中自我报告的睡眠时间、睡眠障碍与空腹及餐后2小时血糖、胰岛素以及糖化血红蛋白浓度之间的关系). (27th November 2013) - Ford, Earl S.; Wheaton, Anne G.; Chapman, Daniel P.; Li, Chaoyang; Perry, Geraldine S.; Croft, Janet B.
Abstract Background There is limited information from population‐based investigations of the associations between sleep duration and sleep disorders and parameters of glucose homeostasis. The objective of the present study was to examine cross‐sectional associations between sleep duration and sleep disordered breathing with concentrations of insulin, fasting and 2‐h glucose, and HbA1c. Methods Data from 11 815 adults aged ≥20 years without diagnosed diabetes (5002 with an oral glucose tolerance test) from the National Health and Nutrition Examination Survey 2005–2010 were used. Information about sleep duration (2005–2010) and sleep apnea and sleep‐disordered breathing (2005–2008) was obtained via questionnaire. Results An estimated 36.0% of participants reported sleeping ≤6 h/night, 62.0% reported sleeping 7–9 h/night, and 2.0% reported sleeping ≥10 h/night. In 2005–2008, 33.0% reported snoring ≥5 nights per week, 5.9% reported they snorted, gasped, or stopped breathing ≥5 nights/week, and 4.2% reported sleep apnea. Sleep duration was significantly associated with fasting concentrations of insulin and concentrations of HbA1c only in models that did not adjust for body mass index (BMI). Concentrations of fasting and 2‐h glucose were significantly associated with sleep duration in models that adjusted only for age. Snoring frequency was positively associated with concentrations of insulin and HbA1c. Frequency of snorting or stopping breathing and sleep apnea status were associated with concentrations of insulin and of HbA1c only when BMI was not accounted for. Conclusion In a representative sample of US adults, concentrations of insulin and HbA1c were significantly associated with short sleep duration, possibly mediated by BMI.